A New Lycid Genus from the Dominican Amber (Insecta, Coleoptera, Lycidae, Leptolycinae, Leptolycini) - Sergey V. Kazantsev (Psyche: A Journal of Entomology)
A new fossil genus, Electropteron  gen.n., and a new species, E. avus  sp.n., are described from the Dominican Amber. Electropteron avus  gen.n., sp.n., appears to be related to some of the extant Great Antillean lycids and is the first fossil taxon from the subfamily Leptolycinae.